Lesson Study Dalam Peningkatan Kualitas Pembelajaran di Madrasah Ibtidaiyah Maâarif Kejiwan Wonosobo - Muntaqo, Rifqi; Masruroh, Dwi (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2016)
This research analyzes the lesson study learning model implemented in MI Maarif Kejiwan Wonosobo an effort to improve the quality of learning and student achievement. This research aims to determine aspects of school management that occurred in MI Maarif Kejiwan Wonosobo in the implementation of lesson study. This research is a qualitative field research, data collection techniques as for the emphasis on participant observation, interview and documentation. Data analysis techniques used by Miles and Huberman, analysis consists of three activities, namely the flow of data reduction, data presentation, and conclusion or verification. This research is a case study because the focus of this research is to answer the question